Perceptions of Chinhoyi University of Technology’s staff and students regarding the Communication Skills course (International Journal of Scientific Research and Management (IJSRM), 2018)
This study explores the myriad of perceptions, perspectives, attitudes, approaches and conceptions about the module Communication Skills (CUACE101) which is a campus-wide compulsory course taught to all Chinhoyi University of Technology first year first semester (1.1) students. The motivating factor for this study has been an endless debate on the merits of the course to a university curriculum whose niche and mandate is predominantly technology-oriented, hence the need to establish the rationale for a communication course appropriately packaged to yield not only a fully qualified graduate but also a wholesome citizen whose harmonious combination of well-accentuated faculties fits them for an indelible impress on a career terrain tilted in the direction of twenty-first century global imperatives. The research thus motivates for a perceptive shift from a fragmented and compartmentalized view of a university graduate, embracing rather the merits of higher education’s systemic vision driven by a synthesis of multi-disciplinary curriculum design dynamics. Inspired by the Reconstructionist philosophy, this qualitative exploratory study yields a taxonomy of themes and trends by respondents from various disciplines at Chinhoyi University of Technology, necessitating a broad-based and holistic approach to university curriculum programming. The global currents have triggered a paradigm shift from the instruction of communication as a course in commonplace literacy fundamentals (reading, speaking and writing skills) to a more nuanced discipline that factors in a host of globalization-compliant dynamics like information literacy skills, critical thinking skills, people skills, cultural literacy, technopreneurial skills, communicative competence and corporate wisdom. The study deploys focus group discussions (for CUACE101 students) and CUT schools deans questionnaires, triangulating qualitative methods to establish key internal stakeholder perceptions on the campus-wide course (Communication Skills). The study’s findings map out a blue-print for influencing policy and practice in curriculum design, implementation and review